Izpopolnjevanje tehnično-taktičnih elementov košarke s pomočjo iger na en koš s prilagojenimi pravili - Erčulj, Frane (Šport (Ljubljana), 2017)
Basketball games with one basket (1:1, 2:2 and 3:3) are an important element of basketball training as well as the process of learning to play basketball within school physical education. With a smaller number of players and adjusted rules, specific technical and/or tactical elements of basketball can be given more emphasis in certain playing circumstances, while also increasing their frequency (number of repetitions) in a game. The article presents different one-basket games with adjusted rules, which can be used to effectively train and improve different technical and tactical elements of attack (dribbling, throws, passing and receiving the ball, dribble faking, getting open, cutting, crossing, blocking) and of defence. The games with adjusted rules are organised as circuit training activities with an optional number of stations and/or baskets (depending on the available training conditions) and consequently include a higher or smaller number of players (pupils).
Keywords: basketball; košarka; learning; physical education; sport; šport; športna vzgoja; training; trening; učenje